„Occisio Gregorii Vodae…”, între document şi prelucrare literară - Ileana Mihăilă (Revista de Istorie și Teorie Literară)
This is a historical-literary presentation of the first fully conserved Romanian play, Occisio Gregorii in Moldavia Vodae tragedice expressa (c. 1778). Theories concerning the historical conditions of its creation (namely its time, place and author), the display of the facts in comparison to whatever details were included in other historical sources, as well as the issue of its genre all undergo critical analysis. It is then argued that it, in fact, is a mascherata (masquerade), which owes much to the Italian Renaissance tradition of carnival shows bearing this generic name. The Romanian play is more similar to such works than to the Baroque theatre, which had previously been the preferred solution of Romanian researchers of the past decades. Concerning its historical basis, it is shown that, following comparison to contemporary accounts of the death of Grigore III, the prince of Moldavia, the version from Occisio Gregorii has a very similar source to that of Mihail Kogalniceanu’s historical novel, Trii zile din istoria Moldaviei (1844).